Assessment of the low-GWP refrigerants R600a, R1234ze(Z) and R1233zd(E) for heat pump and organic Rankine cycle applications. (25th February 2020) - Longo, Giovanni A.; Mancin, Simone; Righetti, Giulia; Zilio, Claudio; Steven Brown, J.
Highlights: Assessment of refrigerants R600a, R1234ze(Z) and R1233zd(E) for HP and ORC. R1233zd(E) shows higher efficiency than that of R245fa both in HP and ORC. R12343ze(Z) shows similar efficiency than that of R245fa both in HP and ORC. R600a shows lower efficiency than that of R245fa both in HP and ORC. R600a, R1234ze(Z) and R1233zd(E) exhibit very similar condensation performances. Abstract: This paper performs the thermodynamic and the heat-transfer assessment of the low-GWP refrigerants R600a, R1234ze(Z) and R1233zd(E) as alternative to the traditional low-pressure HFC refrigerants, such as R245fa, for Heat Pump (HP) and Organic Rankine Cycle (ORC) applications. The thermodynamic assessment shows that R1234ze(Z) exhibits efficiency very similar to those of R245fa, while R1233zd(E) presents higher efficiency and R600a lower efficiency than those of R245fa both in HP and ORC applications. The heat transfer assessment is carried out in condensation inside a 4 mm ID horizontal smooth tube at three different saturation temperatures (30, 35, and 40 °C), at different vapour qualities and mass velocities. R600a, R1234ze(Z) and R1233zd(E) show very similar condensation heat transfer and pressure drop performances under operating conditions typical for HP and ORC applications. The results of the thermodynamic and the heat transfer assessment show that R600a, R1234ze(Z) and R1233zd(E) are valuable long-term low-GWP substitutes for the traditional low-pressure HFC refrigerants, both in HP and ORC applications.